Teachers’ self-efficacy: How does it predict children’s task persistence and behavioral self-regulation? - Davolytė, Justina; Raižienė, Saulė; Šilinskas, Gintautas (Psichologija, 2020)
It has been suggested that the quality of pre-primary education influences children’s learning abilities in a variety of ways. Teachers’ behaviors are among the major factors relating to the quality of the classrooms, and one aspect of them – teachers’ self-efficacy – has been put forward to predict successful development of childrens’ learning and abilities to learn. Given this, it is surprising that relatively few studies have taken pre-primary techers’ self-efficasy into account, and no research on the topic has been conducted in Lithuania. Futhermore, a few studies have analyzed how teachers’ self-efficacy relates to childrens’ learning abilities, such as, tasks persistence and self-regulation. Consequently, the present study analyzed relations between teachers’ self-efficacy, childrens’ task persistence and self-regulation. This study is based on the theory of teachers’ self-efficacy by Tschannen-Moran and Woolfolk Hoy (2001). The aim of the current study is to determine whether the self-efficacy of Lithuanian pre-primary teachers’ is related to the learning outcomes, in particular, childrens’ tasks persistence and ability to regulate their behavior. Childrens’ tasks persistence was measured using the Behavioral strategy rating scale (teachers’ form) (Aunola et al., 2000; Zhang et al., 2011); the Head-Toes-Knees-Shoulders task (McCellandet al., 2007; Ponitz et al., 2008; Ponitz at al., 2009) was used to measure childrens’ self-regulation. Participants were 18 pre-primary education teachers from six Lithuanian schools and their 229 pre-primary class students (116 [50.7%] girls and 113 [49.3%] boys). Teachers answered questionnaires concerning their self-efficacy towards the whole class and towards each child’s task persistence; school psychologists tested each child on their self-regulation. The statistical analyses of this study comprised of correlation analyses and hierarchical regression analyses. The results supported our expectations about the positive significant relations between teachers’ self-efficacy, childrens’ tasks persistence and self-regulation. That is, the greater teachers’ self-efficacy was, better childrens’ tasks persistence and self-regulation were. The results stayed significant even after controlling for, child gender, parental education, and teachers’ experience. MoreoverIn particular, gilrs and children of higher educated parents were more likely to have better task persistence and self-regulation. Moreover, surprisingly, it was found that teachers’ work experience predicted childrens’ self-regulation. Taken together, the results have verified that techers’ self-efficacy plays a meaningful role in promoting childrens’ tasks persistence and self-regulation in Lithuanian preschool. Thus, from the practical point of view, in order to facilitate children’s learning in preschool and primary school, one should also pay attention to the ways of strengthening teachers’ self-efficacy.